2004
DOI: 10.1063/1.1836001
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency noise mechanisms in Si and pseudomorphic SiGe p-channel field-effect transistors

Abstract: Measurements of low frequency noise in Si and Si0.64Ge0.36 p-channel metal oxide semiconductor field effect transistors are compared with a model of carrier number fluctuations due to tunneling into an energy independent density of oxide trap states (Nox) and associated mobility fluctuations. The failure of the model to explain the data leads us to suggest that reduced noise in the SiGe device as compared to Si is primarily associated with an energy dependence of Nox and a displacement of the Fermi level at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…This has been reported for buried channel Si MOSFETs, 67,[78][79][80] SiGe pMOSFETs, 12,81 SOI four-gate transistors, 82 f completely since the mobility fluctuation noise still remains. However, is it possible that the mobility fluctuation noise is enhanced by the gate oxide interface as well?…”
Section: /F / Noise Dependence On Channel Position Fmentioning
confidence: 71%
See 2 more Smart Citations
“…This has been reported for buried channel Si MOSFETs, 67,[78][79][80] SiGe pMOSFETs, 12,81 SOI four-gate transistors, 82 f completely since the mobility fluctuation noise still remains. However, is it possible that the mobility fluctuation noise is enhanced by the gate oxide interface as well?…”
Section: /F / Noise Dependence On Channel Position Fmentioning
confidence: 71%
“…However, by biasing the surface Si and buried SiGe channel pMOSFETs in an appropriate way so that the quasi-Fermi levels in the two devices are equally distant from the valence band edges, the extracted trap densities would be roughly equal. In a recent publication, 82 Prest and co-workers were successful with this kind of exercise by including a Hooge mobility fluctuation noise term (α H = 2×10 -5 ) also, which was not considered in earlier work.…”
Section: /F Noise Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dominant contribution of contact noise can be found in many publications for different FETs, 21,22) including p-SiGe MOSFETs. 10) However in the devices presented here, noise always decreases with increasing gate voltage overdrive (see Fig. 5) indicating negligible contribution of the contact noise.…”
Section: Resultsmentioning
confidence: 98%
“…6) Due to the relative immaturity of the s-Si technology, noise characterization of these devices is limited. The low frequency noise in p-type strained-SiGe MOSFETs has been studied in multiple papers [7][8][9][10][11][12][13][14] and references therein. However, noise studies in n-channel strained-Si modulation doped FETs (MODFETs) have been reported in a few publications only dealing with Schottky gate devices.…”
Section: Introductionmentioning
confidence: 99%